ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN PENGARUH TINGKAT SUKU BUNGA, NISBAH BAGI HASIL DEPOSITOMUDHARABAH, DAN PERTUMBUHAN EKONOMI TERHADAPPERTUMBUHAN DEPOSITO MUDHARABAH DI BANK SYARIAH MANDIRI PERIODE 2006:01-2011:12 - Iqra Aulia (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2012)
Vector Auto Regression (VAR) is an analysis or statistic method which can be used to predict time series variable and to analyst dynamic impact of disturbance factor in the variable system. In addition, VAR analysis is very usefull to assess the interrelationship between economics variable. This research through the following test phases: unit root test, optimal lag test, granger causality test, and form a vector auto regression model (VAR). The data used in this research is interest rate (i), profit low sharing of mudharabah deposits (nBH), economic growth (gGDP, growth of mudharabah deposits volume (gVM) in the period 2006:01-2011:12. The effectiveness was measured by two indicators. This study used secondary data issued by Syariah Mandiri Bank & Bank Indonesia. The result of the study shows that response velocity of variable in growth of mudharabah deposits volume (gVM) towards shock instrument of interest rate(i) until reach the final target about 4 months. Thus we can conclude that growth of mudharabah deosits volume through Interest Rate is not effective in Indonesia period of 2006:01-2011:12. Keyword: Vector Auto Regression (VAR), growth of mudharabah deposits volume (gVM), The Interest Rate.